2014
DOI: 10.1007/978-1-4939-1804-1_23
|View full text |Cite
|
Sign up to set email alerts
|

Epigenetics in Breast and Prostate Cancer

Abstract: SUMMARY Most recent investigations into cancer etiology have identified a key role played by epigenetics. Specifically, aberrant DNA and histone modifications which silence tumor suppressor genes or promote oncogenes have been demonstrated in multiple cancer models. While the role of epigenetics in several solid tumor cancers such as colorectal cancer are well established, there is emerging evidence that epigenetics also plays a critical role in breast and prostate cancer. In breast cancer, DNA methylation pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
56
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 94 publications
(57 citation statements)
references
References 114 publications
0
56
0
1
Order By: Relevance
“…This suggests that Mfn2 hypoexpression in breast cancer is at least partially attributable to hypermethylaton of its promoter. Although 5-aza-CdR can rescue the expression of tumor suppressor genes by demethylating their promoter CpG sites (24)(25)(26)(27)(28)(29)(30)(31), its clinical anti-tumor applications are limited due to lack of gene specificity. Furthermore, it was reported that Mfn2 is a direct target of miR-761 and upregulation of Mfn2 expression by inhibiting miR-761 repressed hepatocarcinoma growth and metastasis (32).…”
Section: Discussionmentioning
confidence: 99%
“…This suggests that Mfn2 hypoexpression in breast cancer is at least partially attributable to hypermethylaton of its promoter. Although 5-aza-CdR can rescue the expression of tumor suppressor genes by demethylating their promoter CpG sites (24)(25)(26)(27)(28)(29)(30)(31), its clinical anti-tumor applications are limited due to lack of gene specificity. Furthermore, it was reported that Mfn2 is a direct target of miR-761 and upregulation of Mfn2 expression by inhibiting miR-761 repressed hepatocarcinoma growth and metastasis (32).…”
Section: Discussionmentioning
confidence: 99%
“…175 In various cancer models, aberrant DNA and histone modifications have been shown to silence tumor suppressors or promote oncogenes. 176 The three major epigenetic modifications, namely DNA methylation, changes to chromatin, and noncoding RNA profiles, are discussed in this chapter.…”
Section: Epigenetic Basis Of Tcmmentioning
confidence: 99%
“…Aberrant DNA hypermethylation of promoter‐associated CpG islands is characteristic for tumor cells, including PC cells (Jones and Laird, ; Baylin and Herman, ). Promoter hypermethylation is closely associated with gene silencing and may cause downregulation of, for example, tumor suppressor genes during carcinogenesis (Kulis and Esteller, ; Wu et al ., ). Moreover, aberrant promoter hypermethylation of specific genes has been reported to hold promising diagnostic and/or prognostic biomarker potential for PC in tissue samples (Park, ; Sorensen et al ., , ; Strand et al ., ).…”
Section: Introductionmentioning
confidence: 97%